The soul fallacy : what science shows we gain from letting go of our soul beliefs - Musolino, Julien, 1970- (Amherst, New York : Prometheus Books, 2015)
Wat hebben wij te winnen bij het dumpen van ons geloof, zo vraagt Musolino zich af in dit boek.
Lifting the veil -- The spirit of the age -- The first principle -- Dualism on trial -- Requiem for the soul -- La mettrie's revenge -- Descartes' shadow -- The sum of all fears -- Imagine.
Includes bibliographical references (pages 273-280) and index.
Keywords: Religion and science; Soul